The mental health of all children in contact with social services: a population-wide record-linkage study in Northern Ireland - Sarah McKenna; Dermot O’Reilly; Aideen Maguire (Epidemiology and Psychiatric Sciences, 2023)
Abstract Aims Children in contact with social services are at high risk for mental ill health, but it is not known what proportion of the child population has contact with social services or how risk varies within this group compared to unexposed peers. We aim to quantify the extent and nature of contact with social services within the child population in Northern Ireland (NI) and the association with mental ill health. We also examine which social care experiences identify those most at risk.